Role of pituitary hormones in regulating renal vitamin D metabolism in man. Issue 6210 (2nd February 1980) - Brown, D J; Spanos, E; MacIntyre, I
Abstract : Studies in animals and tissue culture have shown the importance of prolactin and growth hormone in regulating renal 1 alpha-hydroxylase activity and plasma concentrations of 1, 25-dihydroxycholecalciferol (1, 25(OH)2D3). Evidence for a similar role for these hormones in man was sought by using a radioreceptor assay to measure plasma 1, 25(OH)2D3 concentrations in 20 normal subjects, 12 patients receiving dialysis, 11 patients with primary hyperparathyroidism, 10 pregnant women, seven women with prolactinoma, and 14 patients with acromegaly. Circulating 1, 25(OH)2D3 concentrations were appreciably raised in the patients with primary hyperparathyroidism and the pregnant women (P less than 0.001), slightly but significantly increased in the patients with prolactinoma (P less than 0.05), and greatly raised in those with acromegaly (P less than 0.001). These results suggest that prolactin and growth hormone are important regulators of renal vitamin D metabolism in the physiological conditions of pregnancy, lactation, and growth in man.